Osteoprotegerin Induces CD34+ Differentiation in Endothelial Progenitor Cells - Boisson-Vidal, Catherine; Benslimane-Ahmim, Zahia; Lokajczyk, Anna; Heymann, Dominique; Smadja, David M. (Frontiers in Medicine, 2018)
Endothelial progenitor cells are the main hypothetical cells that could give rise to vessels and in particular one subtype isolated from peripheral or cord bloods: endothelial colony forming cells (ECFCs). These ECFCs are clonogenic precursors committed to endothelial lineage and have robust vasculogenic properties. However, their low number and poor expansion properties when isolated from human adult bloods, currently limit their use as an autologous cell therapy product. We previously reported that osteoprotegerin (OPG), a well-characterized regulator of bone metabolism, contributes to ischemic tissue revascularization, tumor growth in vivo and potentiates ECFCs proangiogenic properties through the secretion of SDF-1. The current study investigated the role of OPG in ECFCs differentiation and expansion from cord blood CD34+ cells. OPG increased the number of ECFCs after endothelial differentiation of CD34+ cells, enhancing the time of endothelial progenitor cells colonies initial appearance and the growth kinetic of endothelial cell progeny. OPG-exposed ECFCs expressed higher levels of CD34+ compared to control ECFCs. In conclusion, our findings provide novel insights into OPG in regulation of CD34+ progenitor cells. These results give new opportunities for ex vivo expansion of human ECFCs using OPG as a cell culture component for future ECFC product manufacture according to GMP.